Climate changes during the Holocene and their impact on Hydrological systems - Issar, A. (International hydrology series., 2003)
It is now widely accepted that increasing concentrations of greenhouse gases in the atmosphere are causing higher global atmospheric temperatures. However, there is still a great deal of uncertainty about the likely effects of such a temperature rise on climate, and even more about the impacts of climate change and variability on the world's hydrological regimes and socio-economic systems. Studying the effects of climate variability in the past can give clues as to possible future effects. This volume provides a comprehensive review of the effects of climate variability on hydrological and hum.